Traction Performance of Common Formal Footwear on Slippery Surfaces - Shubham Gupta; Subhodip Chatterjee; Ayush Malviya; Arnab Chanda (Surfaces, 2022)
Traumatic injuries caused due to slipping and falling are prevalent in India and across the globe. These injuries not only hamper quality of life but are also responsible for huge economic and compensation burdens. Unintentional slips usually occur due to inadequate traction between the shoe and floor. Due to the economic conditions in low and middle-income countries, the public tends to buy low-cost footwear as an alternative to costly slip-resistant shoes. In this study, ten high-selling formal shoes under $25 were considered. These shoes were tested on three commonly available dry floorings and across contaminated common floor surfaces (i.e., water and floor cleaners). The traction performance of the shoes was quantified by using a biofidelic slip tester. The majority of formal shoes were not found to produce the slip-resistant performance across common slippery surfaces. Shoes with softer outsoles exhibited increased slip-resistant performance (R2 = 0.91). Shoe outsoles with less-to-no treads at the heel region showed poor traction performance as compared to other shoes. The apparent contact area was found as an important metric influencing the slip risks in dry and wet slipping conditions (R2 = 0.88). This research is anticipated to help the public and footwear manufacturers select safer shoes to reduce slip-and-fall incidents.